Clinico-etiological spectrum of constipation in children - Sharma, Shipra; Nirala, Sukhlal; Ratre, Rajendra (International Surgery Journal, 2019)
Background: Childhood constipation is a common problem that has been difficult to define because it may comprise of diverse symptoms, from delay or difficulty in defecation sufficient to cause significant distress, to symptoms of faecal incontinence, displaying of retentive posturing and withholding behaviour to painful defecation and passing of stools so large that they may obstruct the toilet. Knowledge of common etiology of constipation and characteristic presentation may help us in initial management of patient without subjecting them to armour of investigation. Methods: The prospective interventional analytical study conducted in the Department of Surgery and Department of Pediatrics Pt. J.N.M. Medical College and Dr. B.R.A.M Hospital, Raipur (Chhattisgarh), India. Consecutive 81 children with constipation presenting to OPD of pediatrics and pediatric surgery at Dr B.R.A.M Hospital, Raipur (Chhattisgarh), India between January 2010 to January 2011 were included in the study. Results: Mean age at presentation was found overall to be 54.49±10.85 months. Presentation of constipation in boys and girls (44% vs 56% in functional and 54% vs 46% in organic). Of the organic causes Hirschsprung’s disease was the commonest diagnosis made (63%). Other organic causes were Rectal stenosis with anteriorly placed anal canal (1.2%), rectal prolapsed (1.2%), anal fissure (1.2%) and associated with dysgerminoma in pelvic cavity in one case. Conclusions: Assessment and management of pediatric constipation poses many challenges for the practitioner including deciphering whether the problem is organic or non-organic in nature.